2020
DOI: 10.1089/jayao.2019.0133
|View full text |Cite
|
Sign up to set email alerts
|

How Can Health Care Professionals Communicate Effectively with Adolescent and Young Adults Who Have Completed Cancer Treatment? A Systematic Review

Abstract: Communication with teenage and young adult or adolescent and young adult (AYA) patients with cancer is critically important and not consistently taught in health care education. We have developed a local training for medical students to experience and join AYA cancer consultations to improve clinicians' abilities in the future. We have undertaken a systematic review of the literature, to provide a comprehensive overview of studies evaluating communication in this specific patient group, to guide clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
(91 reference statements)
2
21
0
2
Order By: Relevance
“…HCPs admitted that they often turned to the parents for their opinions, even if the patients were 16 years or older and thus legal adults in the context of healthcare in Norway (Norwegian Ministry of Health and Care Services, 2015). The importance of changing this practice was discussed, and is supported by two systematic reviews emphasizing that adolescents want more involvement and decisional authority in their cancer care (Lin et al, 2020;Smith et al, 2020). The young age of the patients, cancer severity and strict treatment protocols are often seen as contributing to the lack of tradition around involving children and adolescents with cancer in shared-decision-making (SDM) (Coyne et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCPs admitted that they often turned to the parents for their opinions, even if the patients were 16 years or older and thus legal adults in the context of healthcare in Norway (Norwegian Ministry of Health and Care Services, 2015). The importance of changing this practice was discussed, and is supported by two systematic reviews emphasizing that adolescents want more involvement and decisional authority in their cancer care (Lin et al, 2020;Smith et al, 2020). The young age of the patients, cancer severity and strict treatment protocols are often seen as contributing to the lack of tradition around involving children and adolescents with cancer in shared-decision-making (SDM) (Coyne et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, on a positive note, a recent systematic review has made recommendations on how HCPs can communicate effectively and facilitate SDM with adolescents and young adults post-cancer (Smith et al, 2020). They recommend e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We identified anxiety, burden, depression, resilience, stress, counseling, measurement, and post-traumatic growth. In 7 meta-analyses [53][54][55][56][57][58][59], child and adolescent cancer survivors were highly likely to experience mood or affective disorders [56], and brain tumor in child and adolescent cancer survivors was significantly associated with anxiety, depression, and health-related QOL, highlighting the importance of psychosocial screening. Furthermore, in 1 systematic review and meta-study [54], dealing with the keyword post-traumatic growth identified in this study, the need for targeted social support, clinical intervention, and education to facilitate posttraumatic growth was suggested through an analysis of 18 studies.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Communication challenges that survivors encounter are exclusion from decision making, vague recommendations about long-term follow-up, and parents' avoidance in discussing late effects with their children. 1,5,6 With Hispanic/Latino populations, YACCSs and parents are more reliant on hospital resources for health information compared with non-Hispanic White populations. 7,8 Language barriers impair effective communication, and language preference in pediatric cancer care may influence communication behaviors, thus contributing to health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other studies revealed that communication between the medical team, YACSSs, and parents about the transition process, follow-up plan, and late effects symptoms were important for a successful transition from pediatric to adult-centered survivorship care and engagement in long-term follow-up care. 6,19,20 Yet, these studies are limited in that they do not explore these relationships among Hispanic/Latino populations, and the one study that focused on Hispanic/Latino survivors and parents was a qualitative study.…”
Section: Introductionmentioning
confidence: 99%